ANALISIS STANDAR PELAYANAN MINIMAL (SPM) BADAN LAYANAN UMUM UNIT PELAKSANA TEKNIS DAERAH (BLUUPTD) TRANSPORTASI BRT DI KOTA SEMARANG - Veronika Gisca Ananda Aura; Nina Widowati (Journal of Management and Public Policy, 2026)
This study aims to analyze the implementation of Minimum Service Standards (SPM) at the Public Service Agency of the Regional Technical Implementation Unit (BLUUPTD) of Bus Rapid Transit (BRT) Transportation in Semarang City and identify factors that support and hinder its implementation. This study uses a quantitative approach with descriptive statistical analysis methods and Importance Performance Analysis (IPA) to evaluate six dimensions of SPM, namely security, safety, comfort, affordability, equality, and regularity. The sampling method used is accidental sampling, the sample calculation method uses the Slovin formula so that this study uses 100 respondents. Data were obtained through distributing questionnaires to Trans Semarang BRT service users and supported by secondary data. The results of the study indicate that although some SPM indicators have been implemented quite well, there is still a gap between service performance and user expectations, especially in aspects of service regularity, schedule accuracy, route network integration, and information availability. Factors that influence the implementation of SPM include human resources, organizational strategy, service systems, and user behavior. Therefore, continuous evaluation and improvement of services are needed to improve the quality and reliability of public transportation in Semarang City.